2019
DOI: 10.24818/amp/2019.32-06
|View full text |Cite
|
Sign up to set email alerts
|

Tax counterbalancing in developing countries the case of Indonesia

Abstract: This research is devoted to test the feasibility of tax counterbalancing policy in developing country with focus on Indonesia. This research is motivated by the fact that the corporate income tax rate in Indonesia is relatively high compared to other south east Asian countries. The method uses the (quadratic) almost ideal demand system which has been widely used to analyze the demand system simultaneously. The estimation usesseemingly unrelated regression estimation approachwith quarterly data during the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The standard Granger causality test results show a unidirectional causality running from government revenue to potential output instead of actual output. It means that government revenue prospectively could be a fiscal stabilizer instrument in the future, as suggested by (Kuncoro, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard Granger causality test results show a unidirectional causality running from government revenue to potential output instead of actual output. It means that government revenue prospectively could be a fiscal stabilizer instrument in the future, as suggested by (Kuncoro, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Kuncoro (2014) indicated that the relative efficiency scores of taxes revenue is lower compared to nontaxes revenue. In his subsequent paper, he alternatively recommends tax counterbalancing as a strategic way not only to manage fiscal deficits but also to enlarge fiscal space (Kuncoro, 2019).…”
mentioning
confidence: 99%
“…(12) where ∆ is the first difference operator and EC it-1 is the error correction component created from the long-run demand system, i. e. the static almost demand system as specified by Equation ( 8). The application of error correction model has been extensively employed not only in the analysis of international reserves (Badinger, 2004;Gosellin and Parent, 2004;Prabeesh et al, 2007;Diwantari, 2010, andOyeniran andAlamu, 2020) but also in the macroeconomic policy (Kuncoro, 2018;2019) and services industry (Yoon and Heo, 2017). It seems more straightforward to directly analyse those variables.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…In this context, the keys priorities of the OECD are green organizational behaviour renewable energy and so on (Ik, In 2020, for the first time since 2016, the U.S.A. ranks first due to a short-term expansion of the fiscal credit program for the production and long-term development of the offshore wind segment, with investments of $ 57 billion planned to install a capacity of up to 30 GW by 2030. China's growth in the renewable energy sector has slowed down, amid the authorities' intentions to phase out subsidies in order to create a more competitive market (Kuncoro, 2019). France has moved from fourth to third place, securing a strong position on energy prices and allocating 1.4 GW capacity to developers in the wind and solar energy segments, in order to eliminate gradually the dependence of its network on nuclear energy.…”
Section: Problem Statementmentioning
confidence: 99%